CD58 Immunobiology at a Glance - Zhang, Yalu; Liu, Qiaofei; Yang, Sen; Liao, Quan (Frontiers in Immunology, 2021)
The glycoprotein CD58, also known as lymphocyte-function antigen 3 (LFA-3), is a costimulatory receptor distributed on a broad range of human tissue cells. Its natural ligand CD2 is primarily expressed on the surface of T/NK cells. The CD2-CD58 interaction is an important component of the immunological synapse (IS) that induces activation and proliferation of T/NK cells and triggers a series of intracellular signaling in T/NK cells and target cells, respectively, in addition to promoting cell adhesion and recognition. Furthermore, a soluble form of CD58 (sCD58) is also present in cellular supernatant in vitro and in local tissues in vivo. The sCD58 is involved in T/NK cell-mediated immune responses as an immunosuppressive factor by affecting CD2-CD58 interaction. Altered accumulation of sCD58 may lead to immunosuppression of T/NK cells in the tumor microenvironment, allowing sCD58 as a novel immunotherapeutic target. Recently, the crucial roles of costimulatory molecule CD58 in immunomodulation seem to be reattracting the interests of investigators. In particular, the CD2-CD58 interaction is involved in the regulation of antiviral responses, inflammatory responses in autoimmune diseases, immune rejection of transplantation, and immune evasion of tumor cells. In this review, we provide a comprehensive summary of CD58 immunobiology.